Career Development Program for Pediatric Hematology/Oncology Fellows - Rima Jubran; Patrick Leavey; A. Ritchey; Jean Tersak; Caroline Hastings; Michael Brionnes; Evan Shereck; Julie Nyquist; Dixie Fisher (Association of American Medical Colleges, 2013)
Abstract Introduction The majority of practicing pediatric oncologists experience moderate or higher levels of burnout. Identifying professional goals, choosing the most fitting type of practice, and achieving work-life balance can help physicians to reduce burnout and improve job satisfaction. We thus created this resource as an educational program for first-year pediatric hematology/oncology fellows to elucidate various career pathways and help them align their values with their planned career choice. Methods First-year fellows from six institutions participated in a four-session pilot program. Before the first session, all participants completed a personal values exercise. The first session (2 hours) included a didactic lecture on scholarship and career pathways. Before the second session, participants interviewed faculty from a variety of institutions representing six career pathways. At the second and third sessions (1 hour each), participants presented information gathered from these interviews. At the concluding fourth session (2 hours), participants completed a self-reflection essay and developed a career plan. The program was evaluated by an assessment of knowledge about career pathways and a satisfaction survey. Results Seventeen first-year fellows completed the program. Thirteen indicated that the program helped them decide what career path they would like to pursue. Completing the values exercise and interviewing faculty were rated as the most helpful components of the program. Discussion Currently, few if any institutions employ a formal career-selection exercise for their fellows. This pilot program can be used as a model to expose fellows to different career paths and options for scholarly activities during fellowship. The resource can be adopted by any training program and is not specifically tailored to pediatric hematology oncology fellows.